Evaluating the Diagnostic Accuracy of McMurray, Apley, and Thessaly Tests Compared to MRI in Meniscal Injury - Chaudhary, Durgesh; Chaudhary, Bandana; Shrestha, Bishal; Bhatta, Keshav; Bista, Sagun; Chaudhary, Dinesh (Journal of Multidisciplinary Research Advancements, 2025)
This study aimed to compare the diagnostic accuracy of standard clinical tests, specifically McMurray’s test, Apley’s compression test, and Thessaly test, with magnetic resonance imaging (MRI) for detecting knee meniscal injuries. A prospective analysis was conducted involving patients with clinical suspicion of meniscal injury. Each participant underwent the selected clinical tests followed by an MRI examination. Each test's sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated using MRI as the reference standard. The study found that among the clinical tests, the Thessaly test at 20 degrees of knee flexion demonstrated the highest sensitivity and specificity, closely followed by McMurray’s test. Apley’s compression test showed lower diagnostic accuracy. The combined use of multiple clinical tests improved diagnostic confidence but did not surpass the accuracy of MRI. While MRI remains the gold standard for diagnosing meniscal injuries, specific clinical tests offer considerable diagnostic value, particularly the Thessaly test. These tests can aid the initial assessment, especially in resource-limited settings where MRI is not readily available.